Legal Protection for Indonesian Labor in Government Policy Regarding the Admission of Foreign Labor in Indonesia - Gesang Sri Wulandari (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2019)
Enactment of Presidential Regulation No. 20 of 2018 reaps the pros and cons in the community. This is not without reason but because of several articles contained in the Presidential Regulation (Perpres) are considered making it easier for Foreign Workers to work in Indonesia. The government policy and legal protection of Indonesian workers are being questioned in relation to the policy of accepting the foreign workers. The method used to examine the problems to be discussed in this study is normative juridical research method which is explained in descriptive analytical technique. Policies carried out by the government when viewed from the existing regulations are made to provide guarantees and rights to foreign workers while working in Indonesia. The acceptance of Foreign Workers in Presidential Regulation No. 20 of 2018 provides conditions that must be complied with by employers and the foreign workers cannot be employed if these conditions are not met. This is a form of government effort as a protection for Indonesian Workers.